Foreign language anxiety among Japanese language learners in IIUM Pagoh - Othman, Najwa Diyana; Abdul Latif @ Bapoo, Lilisuriani (Kulliyyah of Languages & Management, IIUM Pagoh, 2021)
This quantitative research investigated the level of foreign language anxiety (FLA) between different genders of Japanese foreign language learners in the higher education context in Malaysia considering that studies specifically focusing on gender differences in the foreign language anxiety among Japanese language learners is not actively explored in Malaysia. The three factors of foreign language anxiety which are communication apprehension, fear of negative evaluation, and test anxiety are the foundation of this study. The overall sample of this study consisted of 40 students who had taken the Japanese language course offered in a Malaysian higher education institution. The mean scores of the female and male learners were compared to determine if there was a great difference between male and female students in their level of foreign language anxiety based on the three factors. An independent sample t-test was also used to investigate if there were statistically significant differences between the three factors in relation to gender. The findings indicated that there were differences between male and female Japanese language learners in their level of foreign language anxiety for the factors of communication apprehension, fear of negative evaluation, and test anxiety. However, the findings revealed that the differences were not statistically significant and that there was not a great difference for each of the factors between male and female students. The results of the study also revealed that all the respondents regardless of different genders had a moderate level of foreign language anxiety for all the factors which indicated that they were slightly anxious